1998
DOI: 10.1007/s002449900420
|View full text |Cite
|
Sign up to set email alerts
|

Interference by Carbohydrate Substrates, Flavonoids, and Monosaccharide Derivatives on Bacterial β-D-Glucuronidase Assays

Abstract: Most commercially available test kits for water and foodstuffs use beta-galactosidase activity for coliforms and beta-glucuronidase activity for Escherichia coli. We tested the effects on the beta-glucuronidase activity of E. coli W3110 of substances usually present in foods and several synthetic pharmaceutical compounds. Thirteen substances were tested: three carbohydrates, four flavonoids, five monosaccharide derivatives, and dimethyl sulphoxide. In a minimum medium without any other carbon source, glucose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It would be caused by the increase of GUS protein amount in the tissue and/or increase of relative enzyme activity of GUS protein. As there were reports on sucrose treatment which did not promote GUS activities in bacteria (Ku et al 2011;Mariscal et al 1998), we presumed that the GUS protein amount increased and it would be from 0.31 to 214 µg by 6% sucrose treatment in SE leaves by calculation from the data according to Kim et al (1995). These results are supported by previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…It would be caused by the increase of GUS protein amount in the tissue and/or increase of relative enzyme activity of GUS protein. As there were reports on sucrose treatment which did not promote GUS activities in bacteria (Ku et al 2011;Mariscal et al 1998), we presumed that the GUS protein amount increased and it would be from 0.31 to 214 µg by 6% sucrose treatment in SE leaves by calculation from the data according to Kim et al (1995). These results are supported by previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Inhibition of GUS by phenolic compounds was also proposed by Vainstein et al (1993) and Serres et al (1997) as the explanation of the observed reduction of b-glucuronidase activity in transgenic tobacco and cranberry plant extracts when combined with non-transformed carnation plant extracts. Also, Mariscal et al (1998) noted negative effects of three flavonoids, i.e., apigenin, kaempferol and quercetin on bglucuronidase enzyme activity. In wheat, the highest level of phenolic compounds and flavonoids are found in the endosperm (Adom et al 2003).…”
Section: Discussionmentioning
confidence: 95%
“…For D-gluconic acid, Mariscal et al (1998) reported that it is a very strong inhibitor especially when supplied to the bacterial culture media at concentration of 0.01 mM or higher. In the present study, we show that both glucuronic acid and D-saccharic acid 1,4 lactone are strong inhibitors of b-glucuronidase activity at concentrations 1.0, 2.0, 4.0 mM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations